2011
DOI: 10.1016/j.ejso.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral breast recurrence after breast conserving surgery in patients with small (≤2cm) breast cancer treated with modern adjuvant therapies

Abstract: Background: Modern multimodality treatment greatly influences the rate and the predictive factors for ipsilateral cancer recurrence (IBR) after breast conserving surgery. Material and Methods Conclusions:The risk of IBR was low during the first 5 years after breast resection among patients with pT1 breast cancer and treated with modern surgical and adjuvant therapies. The majority IBRs still occur at or close to the prior resection site underlining the importance of local therapies. Omission of radiotherapy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
(37 reference statements)
0
8
1
2
Order By: Relevance
“…Forty-nine studies were excluded from the analysis following intensive review of the full text ( Fig. 1), resulting in 15 suitable studies included in this review ( Table 1) [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…Forty-nine studies were excluded from the analysis following intensive review of the full text ( Fig. 1), resulting in 15 suitable studies included in this review ( Table 1) [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…Individual series comparing rates of LR by molecular subtype following breast conservation report conflicting results (Table ). The studies differ in subtype definition and contain a relatively small number of patients with triple negative and HER2/neu overexpressing cancers, and all contain patients treated prior to the routine use of trastuzumab . A meta‐analysis by Lowery et al examined the influence of subtype defined as luminal (ER+/PR+/HER2/neu+/−), triple negative (ER−/PR−/HER2/neu−), and HER2/neu overexpressing (ER−/PR−/HER2/neu+) on LRR in 12,592 women from 15 studies with a median follow‐up of 57 months.…”
Section: Molecular Subtype and Locoregional Recurrencementioning
confidence: 99%
“…Therapeutic de‐escalation is made possible by advances such as standardization of patients screening, emergence of oncoplastic techniques, as well as molecular and genomic profiling. In this prospect, the concept for IORT has been developed after studies showed that local recurrences were more likely to appear in index breast quadrant Indeed, IORT allows the administration of a high radiation dose in the tumor bed, with a good conformation and rapid dose attenuation. In the pilot study, Vaidya et al reported that 5 Gy dose can be administered for about 20 min at 1 cm from the margins of 35 mm cavity.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of systematic screening and emergence of oncoplastic techniques, more patients were eligible for BCS and radiation therapy. 4 This change in the practice pattern has been associated with less surgical morbidity and better quality of life (QOL) for patients 5,6 However, conventional whole breast radiation therapy requires a daily radiation dose (1.8-2 Gy) for 5-6 weeks (50 Gy on whole breast and additional [10][11][12][13][14][15][16] Gy boost on the tumor bed). The result is fatigue and lower QOL for patients, 7 inequalities in access to radiotherapy centers, 8 and increase in medical costs 9,10 In order to further improve the patient's acceptance of radiation treatment, hypofractionation and partial breast irradiation have been developed.…”
Section: Introductionmentioning
confidence: 99%